Aesthetic Radiofrequency Associated with Supplementation is Safe and Reduces Oxidative Stress in Women: Randomized, and Double-Blind Clinical Trial - Greissi Tatieli Franke Tremêa MS; Karine Raquel Uhdich Kleibert MS; Lenara Schalanski Krause BSc; Ana Paula Weber Fell BSc; Anais Regina Scapini BSc; Keli Wilchen Marschall BSc; Cristiano Sartori Baiotto MS; Martha Héllen Tremêa da Silva BSc; José Antonio Gonzalez da Silva PhD; Christiane de Fátima Colet PhD (SAGE Publishing, 2024)
The objective were to evaluate the effects of supplementation of standardized dry extract of Rosmarinus officinalis (RO) and the application of aesthetic radiofrequency on the oxidative stress markers catalase (CAT), superoxide dismutase (SOD), non-protein thiols (NP-SH), and thiobarbituric acid reactive species (TBARS) and the biochemical markers triglycerides, total cholesterol, high density lipoprotein (HDL) cholesterol, glutamic-oxaloacetic transaminase (TGO/AST), pyruvic-glutamic transaminase (TGP/ALT), gamma glutamyl transpeptidase (gamma-GT), and creatinine. This study included 32 women received the aesthetic therapy to reduce localized fat. They were divided into the control group (n = 8) receiving placebo capsules and the intervention group (n = 24) subdivided into Group A, B, and C, each with eight members receiving supplementation with 100, 500, and 1000 mg/day of standardized dry extract of RO, respectively. The Universal Trial Number (UTN) - U1111-1274-6255. Supplementation with RO (500 mg/day) demonstrated a reduction in oxidative stress (quantified with through a significant increase in NP-SH and a reduction in SOD and CAT enzymes). The radiofrequency aesthetic treatment did not promote an increase in oxidative stress; however, it caused significant changes in total cholesterol, HDL cholesterol, and creatinine. RO is a plant with antioxidant effects and its oral consumption is safe in selected women subjects in hepatic and renal markers.